2022
DOI: 10.1002/cctc.202200218
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Fe Species Structure‐Performance Relationship for Direct Methane Conversion toward Oxygenates over Fe‐MOR Catalysts

Abstract: Direct oxidation of methane to value-added products under mild conditions remains a grand challenge due to the problem of selective CH 4 activation. Here we report a Fe-MOR-F catalyst prepared via freeze-drying method, indicating excellent catalytic performance for the direct partial oxidation of methane using H 2 O 2 under mild conditions. Various characterizations including XRD, NH 3 -TPD, H 2 -TPR, UV-Vis, XPS, and EPR studies revealed that Fe-MOR-F catalyst possesses more highly dispersed monomeric and dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…On the contrary, Fang et al, based on DFT and spectroscopic analysis, demonstrated that monomeric species can form •OH and •OOH resulting in the formation of CH 3 COOH, while dimeric species produce CH 3 OH via •OH radicals. 237 Yu et al also showed, three synthesis routes named incipient wetness impregnation (IWI), liquid ion-exchange (IE), and solid-state ion-exchange (SSIE) for the synthesis of Fe-ZSM-5 among which SSIE had the highest (71%) population of monomeric species as determined by 57 Fe Mossbauer spectroscopy. 238 Compared to IWI and IE samples, the Fe/ZSM-5 SSE yielded the highest CH 3 OH productivity and selectivity demonstrating the direct role of monomeric species.…”
Section: Characterization Of Sacsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, Fang et al, based on DFT and spectroscopic analysis, demonstrated that monomeric species can form •OH and •OOH resulting in the formation of CH 3 COOH, while dimeric species produce CH 3 OH via •OH radicals. 237 Yu et al also showed, three synthesis routes named incipient wetness impregnation (IWI), liquid ion-exchange (IE), and solid-state ion-exchange (SSIE) for the synthesis of Fe-ZSM-5 among which SSIE had the highest (71%) population of monomeric species as determined by 57 Fe Mossbauer spectroscopy. 238 Compared to IWI and IE samples, the Fe/ZSM-5 SSE yielded the highest CH 3 OH productivity and selectivity demonstrating the direct role of monomeric species.…”
Section: Characterization Of Sacsmentioning
confidence: 99%
“…Many heterogeneous Fe-based zeolite supported catalysts such as Fe-ZSM-5 230−232 and Fe@MFI 233 have been reported for the CH 4 OR. 187 Like Cu-based zeolites, the nature of catalytic centers remains elusive and monomeric, and 237 Yu et al also showed, three synthesis routes named incipient wetness impregnation (IWI), liquid ion-exchange (IE), and solid-state ion-exchange (SSIE) for the synthesis of Fe-ZSM-5 among which SSIE had the highest (71%) population of monomeric species as determined by 57 Fe Mossbauer spectroscopy. 238 Compared to IWI and IE samples, the Fe/ZSM-5 SSE yielded the highest CH 3 OH productivity and selectivity demonstrating the direct role of monomeric species.…”
Section: Characterization Of Sacsmentioning
confidence: 99%
See 1 more Smart Citation